Extensive Cutaneous Scalp Angiosarcoma - Zabeer Bhatti; Rameez Bhatti; Sharon Brangman; Kerry Whiting; Amit Dhamoon (Hindawi Limited, 2018)
Angiosarcoma is a cancer that is derived from endothelial cells that line blood vessels and lymphatic channels. Cutaneous angiosarcoma can appear anywhere on the skin and the clinical presentation is highly variable. Most cases appear on the scalp and face de novo. Our case describes a 91-year-old female with cutaneous scalp angiosarcoma. Our case serves to remind physicians that an abnormal skin finding in older adults should raise their index of suspicion for angiosarcoma and an early biopsy should be performed.